Comparison Between Magnetic Resonance Imaging and Computed Tomography in the Detection and Volumetric Assessment of Lung Nodules: A Prospective Study - Darçot, Emeline; Jreige, Mario; Rotzinger, David C.; Gidoin Tuyet Van, Stacey; Casutt, Alessio; Delacoste, Jean; Simons, Julien; Long, Olivier; Buela, Flore; Ledoux, Jean-Baptiste; Prior, John O.; Lovis, Alban; et al. (Frontiers in Medicine, 2022)
Rationale And Objectives CT lung nodule assessment is routinely performed and appears very promising for lung cancer screening. However, the radiation exposure through time remains a concern. To evaluate the potential of optimized Ultra-short echo time (UTE) MRI for lung nodule detection and volumetric assessment. Materials And Methods Eight (54.9±13.2years) patients with at least 1 non-calcified nodule ≥4mm were included. UTE under high-frequency noninvasive ventilation (UTE-HF-NIV) and in free-breathing at tidal volume (UTE-FB) were investigated along with volumetric interpolated breath-hold examination at full inspiration (VIBE-BH). Three experienced readers assessed the detection rate of nodules ≥4mm and ≥6mm, and reported their location, 2D-measurements and solid/subsolid nature. Volumes were measured by two experienced readers. MR results were compared to gold-standard CT data. Results UTE-HF-NIV provided the highest detection rate for nodules ≥4mm (n=66) and ≥6mm (n=32) (35% and 50%, respectively). No dependencies were found between nodule detection and their location in the lung with UTE-HF-NIV (p>0.4), such a dependency was observed for two readers with VIBE-BH (p=0.002 and 0.03). Dependencies between the nodule’s detection and their size were noticed among readers and techniques (p<0.02). When comparing nodule volume measurements, an excellent concordance was observed between CT and UTE-HF-NIV, with an overestimation of 13.2% by UTE-HF-NIV, <25%-threshold used for nodule’s growth, conversely to VIBE-BH that overestimated the nodule volume by 28.8%. Conclusion UTE-HF-NIV is not ready to replace low-dose CT for lung nodule detection, but could be used for follow-up studies, alternately with CT, based on its volumetric accuracy.